2001
DOI: 10.1097/00006454-200108000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae type b disease: impact and effectiveness of diphtheria-tetanus toxoids-acellular pertussis (-inactivated poliovirus)/ H. influenzae type b combination vaccines

Abstract: Although it is well-documented that DTaP/Hib vaccines elicit lower anti-Hib titers than separate vaccines, such combinations are effective in reducing the incidence of invasive H. influenzae type b disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 18 publications
2
16
0
4
Order By: Relevance
“…Furthermore, in countries such as Germany where the combined DTPa/Hib vaccine has been implemented into national immunization program, no increase in the incidence of Hib infections in comparison with time when Hib was given as a separate injection has occurred. 11 Another interesting finding described also in some previous studies [1][2][3]12 was a significantly lower and most likely clinically irrelevant antibody response to TT after combined administration of DTPa and Hib as compared with separate administration. Reasons and mechanisms of such interference have been extensively studied in animal models and showed that suppression of PRP is a plausible result of interaction between the Hib and TT components.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, in countries such as Germany where the combined DTPa/Hib vaccine has been implemented into national immunization program, no increase in the incidence of Hib infections in comparison with time when Hib was given as a separate injection has occurred. 11 Another interesting finding described also in some previous studies [1][2][3]12 was a significantly lower and most likely clinically irrelevant antibody response to TT after combined administration of DTPa and Hib as compared with separate administration. Reasons and mechanisms of such interference have been extensively studied in animal models and showed that suppression of PRP is a plausible result of interaction between the Hib and TT components.…”
Section: Discussionsupporting
confidence: 52%
“…Firstly, demonstration of induction of immune memory with an anamnestic response on challenge [8,9,20,31] suggests that achieving certain predefined levels of circulating antibody may not be essential for individual protection. Secondly, the failure so far of surveillance data to show any increase in incidence of Hib disease in countries using DTPa-based Hib combinations [26] or in countries not routinely recommending a Hib booster in the 2nd year of life [15], offers hope that reduced Hib immunogenicity does not impair control of Hib disease at the individual or the population level. However, it must be recognised that several more years of surveillance will be required to obtain definitive answers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these responses were also similar to those induced by the DTPw-based Hib vaccine. These data, along with postmarketing confirmation of ongoing vaccine effectiveness in Germany (30), attest for the excellent clinical effectiveness of DTPa-based Hib combination vaccines in preventing Hib disease in infants and children.…”
Section: Discussionmentioning
confidence: 66%